2014
DOI: 10.1530/endoabs.35.p1129
|View full text |Cite
|
Sign up to set email alerts
|

The role of ATM-CHEK2-BRCA1 axis in determination of genetic predisposition and clinical presentation of papillary thyroid carcinoma

Abstract: The risk of developing papillary thyroid carcinoma (PTC), the most frequent form of thyroid malignancy, is elevated up to 8.6-fold in first-degree relatives of PTC patients. The familial risk could be explained by high-penetrance mutations in yet unidentified genes, or polygenic action of low-penetrance alleles. Since the DNA-damaging exposure to ionizing radiation is a known risk factor for thyroid cancer, polymorphisms in DNA repair genes are likely to affect this risk. In a search for low-penetrance suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…Of note, the association between the I157T allele and thyroid cancer was also confirmed in a recent study from central Poland of 1,781 patients with papillary thyroid cancer and 2,081 healthy control reported odds ratio of 2.2 (p < 0.0001), but truncating mutations were not analyzed and data on family history and other primary cancers were not provided. 29 CHEK2 mutations are associated with a number of cancers; we found that a positive family history of breast cancer, lymphoma and sarcoma was more common in CHEK2 carriers than in non-carriers and the difference was significant (p < 0.05). Also carriers reported more frequently family history of thyroid cancer, prostate cancer and endometrial cancer.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Of note, the association between the I157T allele and thyroid cancer was also confirmed in a recent study from central Poland of 1,781 patients with papillary thyroid cancer and 2,081 healthy control reported odds ratio of 2.2 (p < 0.0001), but truncating mutations were not analyzed and data on family history and other primary cancers were not provided. 29 CHEK2 mutations are associated with a number of cancers; we found that a positive family history of breast cancer, lymphoma and sarcoma was more common in CHEK2 carriers than in non-carriers and the difference was significant (p < 0.05). Also carriers reported more frequently family history of thyroid cancer, prostate cancer and endometrial cancer.…”
Section: Discussionmentioning
confidence: 68%
“…In aggregate, these data provide evidence that both truncating and missense mutations of CHEK2 confer thyroid cancer risk, and that a truncating mutation appears to confer a higher risk than the missense mutation. Of note, the association between the I157T allele and thyroid cancer was also confirmed in a recent study from central Poland of 1,781 patients with papillary thyroid cancer and 2,081 healthy control reported odds ratio of 2.2 ( p < 0.0001), but truncating mutations were not analyzed and data on family history and other primary cancers were not provided …”
Section: Discussionmentioning
confidence: 73%
“…The same variant also modifies the risk for ionizing radiation-induced or sporadic papillary thyroid carcinoma in addition to BRCA1 and p53 variants (Akulevich et al, 2009;Wojcicka et al, 2014). Although association of ATM and risk of breast cancer has been reported as well, this was not confirmed in a recent meta-analysis (Gao et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Several germline changes have been reported to predispose to DTC, including variants in microRNA-146a, ATM-CHEK2-BRCA1 pathway, TERT gene, and 5 SNPs pinpointed by GWAS study (2)(3)(4)(5)(12)(13)(14)(15). So far, no study revealed the influence of germline (inherited) variants on the overall mortality of patients with thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%